Gepants for abortive treatment of migraine: A network meta‐analysis. Issue 8 (11th June 2020) - Hong, Peiwei; Tan, Tianlin; Liu, Yao; Xiao, Jing
Abstract: Objectives: To evaluate and compare the efficacy and safety of gepants for abortive treatment of migraine by network meta‐analysis. Materials & Methods: Publications, which were randomized controlled trials (RCTs) about gepants for abortive treatment of migraine, were acquired from Pubmed and Cochrane Library. The literatures screening and quality assessment followed the Cochrane handbook. Review manager 5.3 and Addis v1.16.8 were utilized for data analyzing. Results: Totally, 15 RCTs were included in the network meta‐analysis. The trials enrolled were with high quality. There are 7 treatments were analyzed: BI 44370 TA, MK‐3207, olcegepant, rimegepant, telcagepant, ubrogepant, and placebo. Of these trials, 11, 118 patients and 10, 917 patients were assigned to one of 7 treatments randomly for efficacy assessment and safety assessment, respectively. In meta‐analysis of direct comparisons, all gepants were superior to placebo in achieving pain freedom 2 hr postdose and only rimegepant and telcagepant were higher than placebo in incidence of any adverse events. In network meta‐analysis, the rank best 3 drugs were olcegepant, BI 44370 TA, and MK‐3207 for efficacy outcomes. And the rank best 3 drugs were BI 44370 TA, placebo, and ubrogepant for safety outcomes. Conclusion: Gepants were effective for abortive treatment of migraine. The most effective treatment of gepants for migraine might be olcegepant which were administrated transvenously. And all of gepants were safe for migraine treatment with single dose. Abstract : All gepants were superior to placebo in achieving pain freedom 2 hr postdose and only rimegepant and telcagepant were higher than placebo in incidence of any adverse events.In network meta‐analysis, the rank best 3 drugs were olcegepant, BI 44370 TA, and MK‐3207 for efficacy outcomes. And the rank best 3 drugs were BI 44370 TA, placebo, and ubrogepant for safety outcomes.